Synthesis of calix[4]azacrown substituted sulphonamides with antioxidant, acetylcholinesterase, butyrylcholinesterase, tyrosinase and carbonic anhydrase inhibitory action - Mehmet Oguz; Erbay Kalay; Suleyman Akocak; Alessio Nocentini; Nebih Lolak; Mehmet Boga; Mustafa Yilmaz; Claudiu T. Supuran (Taylor & Francis Group, 2020)
A series of novel calix[4]azacrown substituted sulphonamide Schiff bases was synthesised by the reaction of calix[4]azacrown aldehydes with different substituted primary and secondary sulphonamides. The obtained novel compounds were investigated as inhibitors of six human (h) isoforms of carbonic anhydrases (CA, EC 4.2.1.1). Their antioxidant profile was assayed by various bioanalytical methods. The calix[4]azacrown substituted sulphonamide Schiff bases were also investigated as inhibitors of acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and tyrosinase enzymes, associated with several diseases such as Alzheimer, Parkinson, and pigmentation disorders. The new sulphonamides showed low to moderate inhibition against hCAs, AChE, BChE, and tyrosinase enzymes. However, some of them possessed relevant antioxidant activity, comparable with standard antioxidants used in the study.